The Cultural Construction of Curriculum: Reflections in Latin American Code - Mora Ramírez, Andrés (2014)
This essay develops a number of theoretical and conceptual approaches to the problem of the cultural construction of the curriculum in Latin American. It emphasizes the tensions, trends, omissions and gaps underlying its development. These reflections were developed based on a revision of the state-of-the-art literature which allowed a dialectal approach to the thoughts held by the authors. The critical thinking of these Latin American writers provided significant elements for this interpretative analysis.